Sustainable city compactness evaluation on the basis of GIS and bayes rule - Turskis, Zenonas; Zavadskas, Edmundas K.; Zagorskas, Jurgis (International Journal of Strategic Property Management, 2010)
For a long period in Lithuania there was a tendency to build extensively leaving huge wasteland insertions in the urban fabric of the cities. As a result cities overspread such a big territory that the edges of the cities and location of provision centers are almost inconceivable. In this paper the method of game theory fitted for Geographic Information System (GIS) is given to evaluate and calculate the rate of city compactness. This methodology can help city planners to determine and localize problems of urban fabric density, to enhance motivation and versatility of decisions. For evaluation of city compactness efficiency attributes and the weights of it based on expert judgment are established. This model is applied to Kaunas city. On the basis of GIS the data bank of population, public transport stops and places of public attraction is prepared. Area of the city was divided by rectangular grid and analysis was made calculating efficiency attributes for each sector, applying Bayes rule. The results were visualized as diagrams showing most problematical areas. First Published Online: 18 Oct 2010